Pelaksanaan Supervisi Kelas Kepala Sekolah Terhadap Guru PAI Di Sekolah Dasar Negeri Kecamatan Bukitraya - Hasan Hasan (LPPM STAI Diniyah Pekanbaru, 2019)
This journal is full of rain to provide an overview of the implementation of school principals' supervision to Islamic Education teachers. The principal has functions and duties as an educator, manager, administrator, supervisor, leader, innovator, and entrepreneur, abbreviated as Emaslime. Supervision is a coaching activity that is planned to help teachers and other school staff carry out their work effectively. Class supervision is necessary for schools because it is directly with the treatment, attitude, teaching ability, mastery of the material, classroom management, learning methods, assessment, and others. The purpose of Supervision is, To carry out the tasks following the provisions, procedures, and orders that have been set. So that the results achieved following the objectives set. So that the existing facilities can be utilized effectively and efficiently. To know the weaknesses and difficulties of the organization then look for ways to improve.